A customizable multiplex protein microarray for antibody testing and its application for tick-borne and other infectious diseases - Hari Krishnan Krishnamurthy; Vasanth Jayaraman; Karthik Krishna; Tianhao Wang; Kang Bei; Chithra Changalath; Shiny Matilda; Alex J. Rai; Renata Welc-Falęciak; Agnieszka Pawełczyk; Lucas S. Blanton; Aleš Chrdle; et al. (Scientific Reports)
Abstract Tick-borne infections are the most common vector-borne diseases in the USA. Ticks harbor and transmit several infections with Lyme disease being the most common tickborne infection in the US and Europe. Lack of awareness about tick populations, specific diagnostic tests, and overlapping signs and symptoms of tick-borne infections can often lead to misdiagnosis affecting treatment and the prevalence data reported especially for non-Lyme tick-borne infections. The diagnostic tests currently available for tick-borne diseases are severely limited in their ability to provide accurate results and cannot detect multiple pathogens in a single run. The multiplex protein microarray developed at Vibrant was designed to detect multiple serological antibodies thereby detecting exposure to multiple pathogens simultaneously. Our microarray in its present form can accommodate 400 antigens (molecules that can bind to specific antibodies) and can multiplex across antigen types, whole cell lysates, recombinant proteins, and peptides. A designed array containing multiple antigens of several microbes including Borrelia burgdorferi, the Lyme disease spirochete, was manufactured and evaluated. The immunoglobulin M (IgM) and G (IgG) responses against several tick-borne microbes and other infectious agents were analyzed for analytical and clinical performance. The microarray improved IgM and IgG sensitivities and specificities of individual microbes when compared with the respective gold standards. The testing was also performed in a single run in comparison to multiple runs needed for comparable testing standards. In summary, our study presents a flexible multiplex microarray platform that can provide quick results with high sensitivity and specificity for evaluating exposure to varied infectious agents especially tick-borne pathogens.